2014
DOI: 10.1248/cpb.c13-00897
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-influenza Activities of Novel Baicalein Analogs

Abstract: A series of novel flavones derivatives were synthesized based on modification of the active ingredients of a traditional Chinese medicine Scutellaria baicalensis GEORGI and screened for anti-influenza activity. The synthetic baicalein (flavone) analogs, especially with the B-rings substituted with bromine atoms, were much more potent than oseltamivir or ribavirin against H1N1 Tamiflu-resistant (H1N1 TR) virus and usually with more favorable selectivity. The most promising were 5b, 5c, 6b and 6c, all displaying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…T cells and act as a potent inducer of IFN-c during influenza virus infection [19]. Recently, novel baicalein analogs with B-rings substituted with bromine atoms demonstrated extremely potent activity against influenza H1N1 Tamiflu-resistant virus, indicating that baicalein and its analogs can be favorable alternatives in the management of Tamiflu-resistant viruses [21]. In vitro replication of HIV-1 was suppressed by baicalin when infected cells were treated during the early stage of the virus replication cycle [66].…”
Section: Antiviral Activity Of Flavonesmentioning
confidence: 99%
“…T cells and act as a potent inducer of IFN-c during influenza virus infection [19]. Recently, novel baicalein analogs with B-rings substituted with bromine atoms demonstrated extremely potent activity against influenza H1N1 Tamiflu-resistant virus, indicating that baicalein and its analogs can be favorable alternatives in the management of Tamiflu-resistant viruses [21]. In vitro replication of HIV-1 was suppressed by baicalin when infected cells were treated during the early stage of the virus replication cycle [66].…”
Section: Antiviral Activity Of Flavonesmentioning
confidence: 99%
“…These can serve as a key synthon for various heterocycles like flavones, pyrazolines and aurones. Flavones are known for their antimicrobial 23 , antiviral 24 , anticancer 25 and antiinflammatory 26 properties. Literature data also revealed that chromones substituted with pyrazole nucleus exhibit antimicrobial 27,28 activities.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…Recent studies have focused on the anti-influenza activities of Scutellaria baicalensis-derived compounds and derivatives. In particular, the anti-influenza activities of baicalein and baicalin, components of the roots of Scutellaria baicalensis, have been reported by several groups (Chen et al, 2011;Hour et al, 2013;Sithisarn et al, 2013;Chung et al, 2014;Nayak et al, 2014). Baicalin exerts its anti-influenza virus activity by modulating viral non-structural protein 1 (NS1), which results in the up-regulation of interferon (IFN)induced antiviral signaling and reduced phosphoinositide 3-kinase/Akt (PI3K/Akt) signaling in A549 cells (Nayak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%